2018
DOI: 10.1038/eye.2017.292
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and glaucoma in the United States population

Abstract: PurposeTo evaluate the association between cigarette smoking and glaucoma in the United States population.Patients and methodsUS civilian, non-institutionalized population from 2005 to 2008 administrations of the National Health and Nutrition Examination Survey that were ≥40 years of age with visual fields and optic disc photographs were included. Diagnosis of glaucoma was based on the Rotterdam criteria. Logistic regression modeling was performed to assess the association between glaucoma and smoking history,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 47 publications
1
42
1
1
Order By: Relevance
“…A study by Jung et al found that glaucomatous patients with multiple retinal nerve fiber layer (RNFL) defects had a higher prevalence of concomitant vascular diseases (including HTN, end-stage renal disease or cerebrovascular disease) compared to those with glaucoma and no RNFL defects [59]. Additionally, HTN was found to be a risk factor for reduced RNFL in healthy individuals in the European Eye Epidemiology study [60]. These results highlight the potential role of vascular…”
Section: Systemic Hypertension and Hypotensionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study by Jung et al found that glaucomatous patients with multiple retinal nerve fiber layer (RNFL) defects had a higher prevalence of concomitant vascular diseases (including HTN, end-stage renal disease or cerebrovascular disease) compared to those with glaucoma and no RNFL defects [59]. Additionally, HTN was found to be a risk factor for reduced RNFL in healthy individuals in the European Eye Epidemiology study [60]. These results highlight the potential role of vascular…”
Section: Systemic Hypertension and Hypotensionmentioning
confidence: 96%
“…The analyzed studies did not determine smoking as a risk factor for POAG incidence [46] or progression [43]. However, heavy smoking, which was defined by a greater number of cigarette packs smoked daily was associated with higher odds of glaucoma [60]. With this, the role of cytochrome CYP1B1 was confirmed in primary congenital glaucoma, as it influenced the development of the trabecular meshwork [61,62]; CYP1B1 is also a potential regulator in energy homeostasis that promotes hypertension as well [63].…”
Section: Systemic Hypertension and Hypotensionmentioning
confidence: 99%
“…Although following our methodology identified associations between smoking and the development of a variety of diseases, it found that smoking was protective against glaucoma and cataracts. These findings are surprising, though at least one study has reported similar results regarding glaucoma and the potential protective effect of nicotine [28]. Determining a patient's smoking status (past, present, none) accurately is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Another use of following an unbiased prediction modeling approach is to identify benefits in behavior that is well known to be harmful, such as tobacco use. For example, smoking could be identified as associated with the development of a variety of diseases but protective against others; at least one study reported on the potential protective effect of nicotine against glaucoma [28].…”
Section: Introductionmentioning
confidence: 99%
“…Another use of a discovery engine is its ability to identify benefits in behavior that are well known as harmful, such as tobacco use. For example, smoking could be identified as associated with the development of a variety of diseases, but protective against others; at least one study reported on the potential protective effect of nicotine within the context of glaucoma [28].…”
mentioning
confidence: 99%